Projection of Damaged Visual and Language Regions on Low Trail Making Test Part-B Performance in Stroke Patients - Nishimura, Ayako; Sutoko, Stephanie; Kiguchi, Masashi; Atsumori, Hirokazu; Obata, Akiko; Funane, Tsukasa; Kandori, Akihiko; Mizuguchi, Tomohiko; Shimonaga, Koji; Hama, Seiji; Tsuji, Toshio (Frontiers in Neurology, 2022)
Background: The Trail Making Test Part-B (TMT-B) is an attention functional test to investigate cognitive dysfunction. It requires the ability to recognize not only numbers but also letters. We analyzed the relationship between brain lesions in stroke patients and their TMT-B performance. Methods: From the TMT-B, two parameters (score and completion time) were obtained. Subjects were classified into several relevant groups by their scores and completion times through a data-driven analysis (k-means clustering). The score-classified groups were characterized by low (≤10), moderate (10 < score < 25), and high (25) scores. In terms of the completion time, the subjects were classified into four groups. The lesion degree in the brain was calculated for each of116 regions classified by automated anatomical labeling (AAL). For each group, brain sites with a significant difference (corrected p < 0.1) between each of the 116 regions were determined by a Wilcoxon rank-sum significant-difference test. Results: Lesions at the cuneus and the superior occipital gyrus, which are mostly involved in visual processing, were significant (corrected p < 0.1) in the low-score group. Furthermore, the moderate-score group showed more- severe lesion degrees (corrected p < 0.05) in the regions responsible for linguistic functions, such as the superior temporal gyrus and the supramarginal gyrus. As for the completion times, lesions in the calcarine, the cuneus, and related regions were significant (corrected p < 0.1) in the fastest group as compared to the slowest group. These regions are also involved in visual processing. Conclusion: The TMT-B, results revealed that the subjects in the low-score group or the slowest- group mainly had damage in the visual area, whereas subjects in the moderate- score group mainly had damage in the language area. These results suggest the potential utility of TMT-B performance the lesion site.